Electronic Longitudinal Alcohol Study in Communities (ELAStiC) Wales – protocol for platform development. (2019) - Trefan, Laszlo; Akbari, Ashley; Paranjothy, Shantini; Farewell, Daniel Mark; Gartner, Andrea; Fone, David; Greene, Giles Jeremy; Evans, Anette; Smith, Ann; Adekanmbi, Victor; Kennedy, Jonathan; Lyons, Ronan Anthony; et al.
No abstract available